Effect of an educational strategy aimed at teachers on the management of dentoalveolar trauma in public schools in Villavicencio, Colombia - Márquez-Rodríguez, Paula Andrea; Lara-García, Liceth Marina; Rincón-Piñeros, Oscar Giovanny; Carrillo-Reina, Diana Lucia; Angarita-Díaz, Karen Mercedes; Angarita-Díaz, María del Pilar (Revista Facultad de Odontología Universidad de Antioquia, 2025)
Introduction: Dental trauma is one of the main causes of care in pediatric dentistry, since it has a high rate of occurrence in the educational environment. For this reason, it is important to improve the knowledge and attitudes of teachers on this topic since, depending on the actions implemented, they can determine the good prognosis and professional treatment. For this reason, the objective of this research work was to evaluate the effect of an educational strategy that sought to improve knowledge and attitudes about the management of dentoalveolar trauma (DAT) in school teachers from Villavicencio, Meta, Colombia. Methods: An experimental study was carried out, where 235 teachers from 8 public schools were intervened with an educational strategy and were randomly assigned to a control group, and an experimental group. The two groups received an educational talk and a brochure, but the experimental group received audiovisual reinforcement. To determine the effect of the strategy, knowledge and attitudes about DAT management were measured before, and after the intervention, through a validated questionnaire. Results: Before the intervention, there were no significant differences between the control and experimental groups, indicating similar initial levels. After the implementation of the strategy, both groups demonstrated significant improvements in knowledge and attitudes (p < 0.05), without finding significant differences between the groups (p > 0.05), which suggests that the educational strategy with and without Audiovisual reinforcement was equally effective in both groups. Conclusion: The educational strategy, with or without audiovisual reinforcement, was effective in improving knowledge and attitudes about the management of dentoalveolar trauma in teachers of public schools in Villavicencio, Meta, Colombia.